2017
DOI: 10.3126/hijost.v1i0.25816
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bacterial Uropathogens Among Diabetic Patients Attending Padma Nursing Hospital of Western Nepal

Abstract: Urinary tract infections (UTIs) are common in patients with diabetes mellitus (DM). The propensity of the infection can vary in different individuals especially when there is underreporting from the patients having a risk of acquiring infections. This study was conducted in Padma Nursing Home, Pokhara, Nepal from April to September, 2014. A total of 200 mid-stream urine samples were collected from diabetic patients visiting the nursing home and processed by standard laboratory procedure. Antibiotic susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 6 publications
(6 reference statements)
8
8
0
Order By: Relevance
“…Similar findings were reported by Turan et al, (2008) and Chaudhary et al, (2017). Tamang et al, (2017) et al, 2009). Most of the UTI studies showed higher prevalence of gram negative bacteria than gram positive bacteria (Chaudhary et al, 2017;Tamang et al, 2017;Puri et al, 2006).…”
Section: Occurrence Of Bacteria In Different Age Groupssupporting
confidence: 90%
See 3 more Smart Citations
“…Similar findings were reported by Turan et al, (2008) and Chaudhary et al, (2017). Tamang et al, (2017) et al, 2009). Most of the UTI studies showed higher prevalence of gram negative bacteria than gram positive bacteria (Chaudhary et al, 2017;Tamang et al, 2017;Puri et al, 2006).…”
Section: Occurrence Of Bacteria In Different Age Groupssupporting
confidence: 90%
“…(Chhetri et al, 2011). Similar results were reported by Boyko et al, (2005); Lin et al, (2008); Paryani et al,(2012) and Tamang et al, (2017). Klebsiella species were second common uropathogens (7%) among postmenopausal women.…”
Section: Occurrence Of Bacteria In Different Age Groupssupporting
confidence: 87%
See 2 more Smart Citations
“…A similar pattern of antibiotic susceptibility was reported against uropathogenic E. coli isolates from the International Friendship Children's Hospital, Maharajgunj, Kathmandu, 42 Chitwan Medical College, Bharatpur, Chitwan, 43 and Padma Hospital, Pokhara, Nepal. 44 Klebsiella pneumoniae isolates were highly resistant to third generation cephalosporins (cefixime and ceftriaxone), which may be due to the production of extended-spectrum β-lactamase (ESBL). 45 AMR, including MDR, is a global issue.…”
Section: Discussionmentioning
confidence: 99%